Building Smart and Resilient Communities: Interdisciplinary Innovations for Global Impact - Sheik Mohamed (International Journal Multidisciplinary Science, 2026)
The twenty‑first century is witnessing rapid transformations driven by technological advancements, globalization, urbanization, and environmental change. The integration of artificial intelligence, digital technologies, sustainable practices, and human‑centered approaches has reshaped modern societies. Simultaneously, humanity faces unprecedented challenges such as climate change, resource scarcity, digital inequality, and public health crises. These developments highlight the need for creating smart and resilient communities capable of adapting to dynamic global changes. This article explores the significance of interdisciplinary innovation in building sustainable communities and emphasizes the role of education, technology, research, and international collaboration in shaping a resilient future. Findings suggest that interdisciplinary approaches, community‑engaged research, ethical governance of AI, and international cooperation are essential to ensure that smart communities are also inclusive, equitable, and environmentally sustainable.libguides.unco+1